In vitro release kinetics study of Esomeprazole Magnesium Trihydrate tablet available in Bangladesh and comparison with the originator brand (Nexium®) (Stamford Journal of Pharmaceutical Sciences, 2011)
The main aim of present investigation was to study the dissolution pattern of most commercially available formulations of Esomeprazole in Bangladesh. Commercially available ten national brands and originator brand of esomeprazole magnesium trihydrate tablets were studied in simulated gastric medium (pH 1.2) for first 15 minutes and simulated intestinal medium (pH 6.8) for next 30 minutes time period using USP reference dissolu-tion apparatus (Type II). No brands met the dissolution pattern like the originator brand (E1). But three brands (E3, E6 and E7) were found to be very close to it in terms of dissolution pattern. One brand E11 was found to be sub-standard compared to originator one. Drug release profiles were analyzed for zero order, first order and Higuchi equation to reveal the release kinetics perspective of Esomeprazole magnesium trihydrate enteric coated tablets. It was found that first order kinetics was predominant for E1 (Originator Brand). Zero order and Higuchi release kinetics was predominant release mechanism than first order release kinetics for E2, E4 and E11. First order release kinetics was predominant for rest of the brands (E3, E5, E6, E7, E8, E9 and E10). It was found that drug release of those brands followed moderately diffusion method and concentration dependant from the dosage form. Among all of these locally manufactured Esomeprazole brands E3, E6 and E7 showed compatible dissolution pattern and release kinetics compared with the originator brand. Key words: In vitro dissolution; Market preparations; Kinetics study; Esomeprazole; National brand; Originator brand. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8875 SJPS 2011; 4(1): 79-83